2011
DOI: 10.1037/2160-4134.1.s.48
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to slim images in mass media: Television commercials as reminders of restriction in restrained eaters.

Abstract: Objective:The aim of the present study was to explore the effects of exposure to slim images and diet-related products in commercials on actual food intake in relation to dietary restraint. Design: An experimental design was used, in which food intake was measured in 124 female students who watched either a sad or a neutral movie on television, which was interrupted by either commercials featuring slim models and diet products, or neutral commercials. Subsequently, participants filled out questionnaires on die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
2
19
0
1
Order By: Relevance
“…To this end, choices and eye movements were measured while individuals choose between low and high energy food products in a realistic online supermarket task. Since primes are more likely to affect the behavior of individuals when they activate a goal that is relevant to them (Anschutz, Van Strien, & Engels, 2008;Papies et al, 2010). it was hypothesized that the diet prime would affect choice and visual attention more in individuals high in dietary restraint, i.e., individuals that have the goal to restrict energy intake in order to control body weight (Herman & Mack, 1975).…”
Section: Running Head: Role Of Attention In Goal Primingmentioning
confidence: 99%
“…To this end, choices and eye movements were measured while individuals choose between low and high energy food products in a realistic online supermarket task. Since primes are more likely to affect the behavior of individuals when they activate a goal that is relevant to them (Anschutz, Van Strien, & Engels, 2008;Papies et al, 2010). it was hypothesized that the diet prime would affect choice and visual attention more in individuals high in dietary restraint, i.e., individuals that have the goal to restrict energy intake in order to control body weight (Herman & Mack, 1975).…”
Section: Running Head: Role Of Attention In Goal Primingmentioning
confidence: 99%
“…A good deal of literature has now documented the link between media exposure, internalization of the thin-ideal, and eating pathology (Anschutz, Van Strein, & Engels, 2008;Garner, Garfinkel, Schwartz, & Thompson, 1980;Harrison & Cantor, 1997;Heinberg & Thompson, 1995;Silverstein, Perdue, Peterson, & Kelly, 1986;. For example, several studies have found evidence that the rise in the incidence of eating disorders coincided with a decrease in the body weight of women depicted in the media (Garner et al, 1980;Silverstein et al, 1986) and with an increase in the number of articles concerned with weight-loss diets and exercise in major magazines (Garner et al, 1980;.…”
mentioning
confidence: 95%
“…A possible explanation for better dietary practices among women could be that they are more likely to be mindful of their diet than men are (24). Because women are considered a dependent population group in Saudi, it is not surprising that they more readily adhere to advice about diabetes self-management (18).…”
Section: Explanatory Variablesmentioning
confidence: 99%